Effect of the Concentration Liquid Smoke Tabah Bamboo (Gigantochloa nigrociliata Buse-Kurz) and Cooking Temperature on Quality Se’i of Milkfish - Jakung, Maria Liliosa Yulita; Pudja, Ida Ayu Rina Pratiwi; Kencana, Pande Ketut Diah (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
Milkfish has a savory flavor and taste of chewy meat. Milkfish is classfied as a high - protein and low - fatty fish. Smoking milkfish in one of the effort to increase the added value of special product on change in flavor, visibility, texture, and aroma of smoke to produce a high level of product acceptance. Liquid smoke consist of phenol, carbonyl and organic acids. Liquid smoke comes from stem of bamboo tabah (Gigantochloa nigrociliata Buse - Kurz). The purpose of this research was to know how the effect of liquid smoke with various concentrations and the different of cooking temperature oward quality se’i of milkfish. The used method was complete random design within two faktor. The first factor was the concentration of liquid smoke, consisting of 4%, 6%, and 8%. The second faktors was the cooking temperature, consisting of 60oC, 80oC, and 100oC. The best combination of treatment is 8% concetration liquid smoke and temperature of cooking was 100oC, during 4 hours result moisture content 50.70%, ash 2.70%, pH 5.5, protein 15.91%, visibility 4.53, aroma 4.67, taste 4.53, and texture 4.67.